Compassion, stigma, and professionalism among emergency personnel responding to the opioid crisis: An exploratory study in New Hampshire, USA. Issue 1 (14th January 2022) - Metcalf, Stephen A.; Saunders, Elizabeth C.; Moore, Sarah K.; Walsh, Olivia; Meier, Andrea; Auty, Samantha; Bessen, Sarah Y.; Marsch, Lisa A.
Abstract: Objective: Drug overdoses are the leading cause of death in the United States for those under 50 years of age, and New Hampshire has been disproportionately affected, resulting in increased encounters with the emergency response system. The ensuing impact on emergency personnel has received little attention. The present study aimed to explore the experiences and perspectives of emergency personnel responding to the opioid crisis in NH, with a focus on their views toward people who use opioids. Methods: Thirty‐six emergency personnel (emergency department clinicians, n = 18; emergency medical service providers, n = 6; firefighters, n = 6; and police officers, n = 6) in 6 New Hampshire counties were interviewed about their experiences responding to overdoses and their perspectives on individuals who use opioids. Directed content analysis was used to identify themes in the transcribed, semistructured interviews. The results were reviewed for consensus. Results: Several categories of themes were identified among emergency personnel's accounts of their overdose response experiences and perspectives, including varied degrees of compassion and stigma toward people who use opioids; associations between compassion or stigma and policy‐ and practice‐related themes, such as prehospital emergency care and the role of emergency departments (EDs); and primarily among personnel expressing compassion, a sense of professional responsibility that outweighed personal biases. Conclusions: Despite the magnitude of the ongoing opioid crisis, some emergency personnel in New Hampshire have sustained or increased their compassion for people who use opioids. Others' perspectives remain or have become increasingly stigmatizing. The associations of compassion and stigma with various policy‐ and practice‐related themes warrant further investigation.